Do I Speak Anxiously? A Correlation of Self-Efficacy, Foreign Language Learning Anxiety and Speaking Performance of Indonesian EFL Learners - Anjar Dwi Astuti; Didik Sucahyo; Istanti Hermagustiana (Script Journal: Journal of Linguistics and English Teaching, 2021)
Background: Self-efficacy and foreign language learning anxiety are already known as two importantly affective variables in learning a foreign language. However, little is known about the relationships between the two affective variables with learners’ speaking performance. Therefore, this present study seeks to figure out: the EFL learners’ self-efficacy, foreign language learning anxiety (FLLA), speaking performance, and the correlation between their speaking performance and self-efficacy, speaking performance and FLLA, and self-efficacy and FLLA. Methodology: A correlational design was selected to answer the research questions. Seventy students of the sixth semester got involved in this study. Three research instruments were applied, namely: a self-efficacy questionnaire, a FLLA questionnaire, and one speaking test used to measure students’ speaking performance. Findings: Based on these results, it can be concluded that the null hypothesis (Ho) was rejected, while the alternative hypothesis (Ha) was accepted. Therefore, there was a significantly positive correlation between speaking performance and self-efficacy and a negative correlation between speaking performance and FLLA, and between self-efficacy and FLLA. It means that student with high-level speaking performance will have high-level of self-efficacy. Then, the higher students’ speaking performance is, the lower their FLLA becomes. It is in line with the correlation between students’ self-efficacy and FLLA, that student with high-level of self-efficacy would has low FLLA.